(untitled) (Research, Society and Development, 2022)
The temporomandibular joint, part of the stomatognathic system, is the only mobile joint in the skull, responsible for involving the mandible to two different bones located in the skull (right and left temporal bones). Electromyographic studies (EMG) demonstrate the importance of disocclusion in canines, this occurs due to the reduction of muscle activity during masticatory movements. Muscles such as masseter and temporalis reduced activity in lateral protrusion when canine guidance was performed, leading to a reduction in the appearance of parafunctional activities. The present work aims to review the literature on canine guidance and its clinical relevance, in order to spread knowledge in the academic community. The canine was appointed as the ideal tooth for lateral movement due to its anatomical characteristics, involving large roots, amount of bone support and disposition in the dental arch. The canine guide prevents contact with the posterior teeth, especially on the rocking side.